Assessing the impact of presentation mining on understanding among visual learners - Kasinathan, Vinothini; MEDI, IMRAN; Mustapha, Aida; O’DANIEL, THOMAS PATRICK (School of Engineering, Taylor’s University, 2018)
PowerPoint is popular amongst learners since it helps with content organization and note-taking. This does not imply that learning has been effective for all learners, as not everyone can learn by listening and reading simplified content provided on PowerPoint slides. While it may be effective to the aural/auditory learners from the Visual, Auditory and Kinesthetic sensory (VAK) model, it is less effective for visual learners. This paper assesses the impact of presentation mining, which is a tool that extracts keywords and key phrases from a collection of PowerPoint slides and generates a mind map based on the extracted keywords and key phrases. The target group is visual learners, as visualizing the content of presentation slides in the form of mind maps is hypothesized to improve the learning quality, thus making the materials easier to understand and to memorize. To achieve the objective, a quantitative study was conducted by distributing questionnaires to 80 randomly selected students at Asia Pacific University of Technology and Innovation (APU), in Kuala Lumpur, Malaysia. The results of the research indicated a significant increase of students understanding of the learning materials provided using the proposed tool, although some further work is required to improve the aesthetics of the mind map.